Qualitative study on the influence of mealtime screen exposure on children’s feeding practices: perspectives from paediatricians and speech-language pathologists in Chennai, Tamil Nadu - Krupa Venkatraman; Nathira Fathima; Thangatur Sukumar Hariharan (BMJ Open)
Objective This qualitative research study investigates perspectives on the influence of mealtime screen exposure (MTSE) on feeding practices in children through semi-structured interviews with paediatricians and speech-language pathologists (SLPs).Design This study used a constructivist paradigm and a qualitative research approach, employing thematic analysis, to understand the research objectives from the lens of practitioners. The researchers used transcripts from semistructured interviews to generate themes.Setting This was a multisite, in situ research study conducted in healthcare facilities such as hospitals, private clinics and educational institutions in Chennai, Tamil Nadu, India, between March and April 2023.Participants 24 participants, 12 SLPs and 12 paediatricians, were interviewed. The researchers selected these participants purposively based on their expertise and experience in dealing with children’s feeding practice-related disorders.Results The study identified six themes: limited awareness of MTSE’s effects, cultural expectations on mothers, screen dependency, sensory deprivation, fragile caregiver–child bonding and picky eating tendencies. Key findings reflect a lack of caregiver awareness, sociocultural pressures and the negative developmental impacts of MTSE on children’s feeding practices.Conclusions This study highlights the need for increased awareness among primary caregivers and healthcare professionals regarding the risks of prolonged MTSE. Both paediatricians and SLPs unanimously agree that MTSE can adversely affect feeding practices.